Hypoxamirs in pulmonary hypertension: breathing new life into pulmonary vascular research - Hale, Andrew E.; White, Kevin; Chan, Stephen Y. (Cardiovascular Diagnosis and Therapy; Vol 2, No 3 (September 05, 2012): Cardiovascular Diagnosis and Therapy, 2012)
In mammalian cells, hypoxia, or inadequate oxygen availability, regulates the expression of a specific set of microRNA, which we have previously termed “hypoxamirs”. Over the past five years, the appreciation of the importance of hypoxamirs in regulating the cellular adaptation to hypoxia has grown dramatically. At a cellular level, each hypoxamir can simultaneously regulate expression of multiple (>100) target genes in order to control fundamental biological processes, including survival, proliferation, angiogenesis, migration, and metabolism, among others. A maladaptive imbalance of these hypoxic phenotypes often drives many ischemic cardiovascular diseases, such as pulmonary hypertension—an enigmatic vascular disorder characterized by pronounced and severe panvasculopathy secondary to diverse upstream etiologies, notably including hypoxia. Yet, despite this pathogenic relationship between hypoxic cell phenotypes and disease, the mechanistic roles of hypoxamirs in modulating pulmonary hypertension remain largely unrecognized. Some advances have been made regarding the contributions of specific hypoxamirs in the development and progression of pulmonary hypertension. New methods are also being developed to more comprehensively study their roles in this complex disease. As a result, a more sophisticated understanding of their pervasive roles in pathogenesis could set the stage for unique diagnostic and therapeutic strategies in pulmonary hypertension.